2022
DOI: 10.1186/s12877-022-03144-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral anticoagulant use among people with and without Alzheimer’s disease

Abstract: Background Although cardio- and cerebrovascular diseases are common among people with Alzheimer’s disease (AD), it is unknown how the prevalence of oral anticoagulant (OAC) use changes in relation to AD diagnosis. We investigated the prevalence of OAC use in relation to AD diagnosis in comparison to a matched cohort without AD. Methods Register-based Medication use and Alzheimer’s disease (MEDALZ) cohort includes 70 718 Finnish people with AD diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, it is important to acknowledge that simply lowering plasma fibrinogen levels may interfere with the crucial role of fibrinogen in coagulation function, consequently increasing the risk of hemorrhagic disorders. An epidemiological survey investigating the use of oral anticoagulants in patients with AD and non-AD patients revealed a gradual decrease in the proportion of patients utilizing oral anticoagulants 2 years after an AD diagnosis, potentially influenced by factors such as the heightened risk of falls in patients ( Ali Babar et al, 2022 ). Particularly in elderly patients, AD brains are prone to hemorrhage due to the presence of cerebral amyloid angiopathy (CAA) ( Thal et al, 2008 ; Smith and Greenberg, 2009 ; Attems et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to acknowledge that simply lowering plasma fibrinogen levels may interfere with the crucial role of fibrinogen in coagulation function, consequently increasing the risk of hemorrhagic disorders. An epidemiological survey investigating the use of oral anticoagulants in patients with AD and non-AD patients revealed a gradual decrease in the proportion of patients utilizing oral anticoagulants 2 years after an AD diagnosis, potentially influenced by factors such as the heightened risk of falls in patients ( Ali Babar et al, 2022 ). Particularly in elderly patients, AD brains are prone to hemorrhage due to the presence of cerebral amyloid angiopathy (CAA) ( Thal et al, 2008 ; Smith and Greenberg, 2009 ; Attems et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that intermediate or high bleeding risk predicted by the ATRIA risk score was associated with a significantly higher prevalence of OAC discontinuation before hospice enrollment. Prior research suggests potential contributing factors to OAC discontinuation among the older‐old, those with cognitive impairment, and those with functional limitations include concerns regarding fall risk and subsequent bleeding 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests potential contributing factors to OAC discontinuation among the older-old, those with cognitive impairment, and those with functional limitations include concerns regarding fall risk and subsequent bleeding. [35][36][37] More than 40% of nursing home residents who discontinued OACs before hospice enrollment had mild cognitive impairment or were cognitively intact. The decision to use OACs to prevent an ischemic stroke has the potential to meaningfully preserve functioning, cognition, and quality of life.…”
Section: Factors Associated With Discontinuation Of Oac Usementioning
confidence: 99%
“…Hence, direct oral anticoagulants (DOACs), which are more often used now, require less monitoring and might even be safer for AD patients who are more susceptible to AD complications. 133 Furthermore, treatment with warfarin (a vitamin K inhibitor) or rivaroxaban (a Factor Xa blocker) decreased the maximal EAE score compared with the control group and decreased inflammatory lesions in the spinal cord in SJL/J EAE mice. Hence, warfarin and rivaroxaban anticoagulation dual therapy could potentially improve MS complications.…”
Section: Other Pathway Inhibitorsmentioning
confidence: 99%
“…In a recent study, Babar et al reported a significant risk of falling issues that may result from the decline in oral anticoagulant use among AD patients after diagnosis. Hence, direct oral anticoagulants (DOACs), which are more often used now, require less monitoring and might even be safer for AD patients who are more susceptible to AD complications 133 . Furthermore, treatment with warfarin (a vitamin K inhibitor) or rivaroxaban (a Factor Xa blocker) decreased the maximal EAE score compared with the control group and decreased inflammatory lesions in the spinal cord in SJL/J EAE mice.…”
Section: Synthetic Antiplatelet Molecules For Nddsmentioning
confidence: 99%